2021
DOI: 10.3390/cancers13040616
|View full text |Cite
|
Sign up to set email alerts
|

Microbe–Mucus Interface in the Pathogenesis of Colorectal Cancer

Abstract: Overlying gastrointestinal epithelial cells is the transparent mucus layer that separates the lumen from the host. The dynamic mucus layer serves to lubricate the mucosal surface, to protect underlying epithelial cells, and as a transport medium between luminal contents and epithelial cells. Furthermore, it provides a habitat for commensal bacteria and signals to the underlying immune system. Mucins are highly glycosylated proteins, and their glycocode is tissue-specific and closely linked to the resident micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 143 publications
(200 reference statements)
0
25
0
Order By: Relevance
“…In addition, recent studies have shown that bacterial biofilms are associated with human colon cancer [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies have shown that bacterial biofilms are associated with human colon cancer [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies have shown that bacterial biofilms are associated with human colon cancer [ 21 , 22 ]. Mucus-invasive bacterial biofilms, for example, were found on the colon mucosa of CRC patients more frequently than in healthy subjects [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Future experiments are essential to determine whether bacterial translocation in this model is the cause of immune cell activation. Finally, it is also possible that the result described here is an artefact of the monolayer model; bacterial contact with the apical membrane of the colonic epithelium is minimal in vivo due to the epithelium structure and secretion of both mucus and antimicrobial components, 22 or that effects observed from the co‐culture of F. prausnitzii are specific to that species of commensal bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Akkermansia muciniphila ( A. muciniphila ) is a member of beneficial microbiota and a dedicated intestinal mucin degrader ( 171 ). Abnormal production and expression of mucin damage the mucinous layer, bringing bacteria into close contact with the intestinal epithelial cells and possibly triggering adverse host response and subsequent CRC development ( 172 ). BBR has been revealed to increase the growth of the populations of the symbiotic genus Akkermansia ( 173 ) and may further have effects on mucin expression.…”
Section: Colorectal Cancermentioning
confidence: 99%